Knowledge of Feeding Practices and the Development of Stunting Toddlers Ages 24-59 Month: Pengetahuan Ibu tentang Pemberian Makan Anak dan Perkembangan Balita Stunting Usia 24-59 Bulan - Mellyani, Jhein; Ansar; Kusumawati, Dwi Erma (Svasta Harena: Jurnal Ilmiah Gizi, 2021)
Mother's knowledge about feeding and developing stunting toddlers in Sigi Regency is not widely known. The purpose of this study was to determine the mother's knowledge about child feeding and the development of stunting toddlers aged 24-59 months in the working area of ​​the Kamaipura Public Health Center, Tanambulava District. This research is descriptive research in the form of a survey, conducted in April - May 2021, in five villages located in Tanambulava District. The population in this study were all stunting toddlers aged 24-59 months totaling 45 people. The sampling technique used was non-probability sampling, by directly interviewing mothers of children under five about the knowledge of child feeding using a questionnaire and measuring the development of stunting under five with a pre-screening development questionnaire according to the age group. Data analysis used univariate analysis. The results showed that the mother's knowledge about child feeding was still not good at 57.8%. Meanwhile, the results of measuring the development of stunting toddlers are in the dubious category of 62.2%. Based on the results of this study, it can be concluded that the knowledge possessed by mothers of toddlers about child feeding is classified as poor, and the development of stunting toddlers is categorized as dubious. Suggestions are expected for nutritionists or midwives to provide feeding practices counseling to mothers of toddlers and to conduct developmental counseling to mothers of stunting toddlers.